Depiction of Surasundaris on the walls of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
At the rear of Shiva Temple 1, depictions of surasundaris (celestial damsels) adorn the walls of the garbhagriha (sanctum sanctorum). They are presented standing gracefully, holding a flower stalk in one hand and grasping the edge of the scarf with the other. The rhythmic composition is achieved through the flexed postures, flowing scarves, and curved flower stalks.